2021
DOI: 10.3390/tropicalmed6040173
|View full text |Cite
|
Sign up to set email alerts
|

Trends of HIV Mortality between 2001 and 2018: An Observational Analysis

Abstract: Since the beginning of the epidemic in the early 1980s, HIV-related illnesses have led to the deaths of over 32.7 million individuals. The objective of this study was to describe current mortality rates for HIV through an observational analysis of HIV mortality data from 2001 to 2018 from the World Health Organization (WHO) Mortality Database. We computed age-standardized death rates (ASDRs) per 100,000 people using the World Standard Population. We plotted trends using locally weighted scatterplot smoothing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…In 2020, 680,000 HIV/AIDS-related deaths were reported worldwide [34]. One of the most fatal events is the death of patients with HIV, since the available treatment offers the same survival as patients without HIV infection, and there is a rising number of deaths in developing countries [35,36]. Our study found a low mortality rate with 6.8% (11 individuals) of military personnel dying from HIV-related infection and comorbidities.…”
Section: Discussionmentioning
confidence: 62%
“…In 2020, 680,000 HIV/AIDS-related deaths were reported worldwide [34]. One of the most fatal events is the death of patients with HIV, since the available treatment offers the same survival as patients without HIV infection, and there is a rising number of deaths in developing countries [35,36]. Our study found a low mortality rate with 6.8% (11 individuals) of military personnel dying from HIV-related infection and comorbidities.…”
Section: Discussionmentioning
confidence: 62%
“…Third, TB mortality among HIV-positive persons is hard to measure, even when Vital registration (VR) systems are in place because deaths among HIV-positive persons are coded as HIV deaths, and contributory causes (e.g., TB) are often not reliably assessed or recorded. To achieve comparability over time, WHO has tried to standardize ICD-10 coding for HIV with detailed guidelines [ 35 ]. TB deaths among HIV-positive persons are estimated by WHO as either direct measurements from VR or indirect estimates from multiplying estimates of TB incidence by the estimates of the case fatality rate [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the observational nature of this study, we do not attempt to attribute causality. As discussed in our previous study, issues exist regarding death certification for HIV [24,50]. However, the WHO has developed computerized coding of the verbal autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized the WHO Mortality Database for the member nations whose data was available. Our current study is based on our recent analysis of trends of HIV mortality [24]. The mortality data were extracted in October 2020 with available data from the WHO mortality database from 2001 and 2018 based on the International Classification of Diseases (ICD) version 10 coding system.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation